CORRELATING BREATHING PATTERN WITH DIFFERENT MALOCCLUSIONS AMONG PATIENTS REPORTING AT DEPARTMENT OF ORTHODONTICS AYUB MEDICAL COLLEGE, ABBOTTABAD, PAKISTAN - Noor, Nabbiya; Zubair, Asifa; Ijaz, Wasim (Journal of Ayub Medical College Abbottabad, 2021)
Background: The present era has been commanded by ample studies correlating breathing modes & risk of occurrence of malocclusion. The early intervention of altered breathing patterns can head off the long-lasting effects of already established malocclusion. The main intention of this project was to establish the possible correlation between mouth-breathing & malocclusions. Methods: Sixty-two (62) patients undergoing orthodontic treatment were evaluated via data form (including history & clinical evaluation). SPSS software version 25.0 was used for data analysis. Patient's age, gender, type of Angle's malocclusion & breathing pattern was taken in account while analysing data. Descriptive statistics & Chi- Square test was applied on the data. It was anticipated that mouth breathing is associated with malocclusion. p-value of less than 0.05 was considered to be statistically significant. Results: A total of 29 males & 33 females participated in the study. The mean age was 13 years (range 6-20 years). A significant correlation was found between mouth-breathing, tongue thrust (p=0.03) & bleeding gums (p=0.006). Other parameters had no significant correlation with mouth-breathing. Conclusion: The current study revealed that mouth breathing has significant association with opened mouth at rest & gingival abnormalities (bleeding/ swollen gums) implying that timely diagnosis of such abnormal breathing pattern can hinder with development of altered occlusion & dentofacial conformation.